Important Aspects Of Increasing The Effectiveness Of Teaching Physical Education In General Secondary Schools (Journal of Pedagogical Inventions and Practices, 2025)
This article discusses the new opportunities created in the field of physical education and sports for physical education teachers and students of general secondary schools, in accordance with the Resolution No. PQ-392 of the President of the Republic of Uzbekistan dated November 15, 2024, “On Fundamental Improvement of Teaching the Subject of Physical Education in General Secondary Schools and Measures to Develop the Professional Activity of Teachers of This Subject.” It also addresses the fundamental reforms in the teaching of physical education and the key tasks to be addressed in the future